The role of vitamin D in the aetiology of type 1 diabetes in the South African Indian and White population - Malaza, Nompumelelo Lebogang (My University, 2019)
Background: Type 1 diabetes (T1D) is a T-cell mediated autoimmune disease characterised by the presence of autoantibodies to β cell antigens such as insulin, glutamic acid decarboxylase and most recently zinc transporter 8 (ZnT8). The exact aetiology of T1D is not fully understood. Recently, vitamin D has been implicated in the development of the disease. Vitamin D is a steroid hormone with a wide range of biological functions including immunoregulation. Vitamin D exerts its immunomodulatory effects by binding to the vitamin D receptor (VDR) which activates a cascade of downstream signalling events. Vitamin D downregulates the expression of pro-inflammatory cytokines resulting in a shift from the T helper 1 (Th1) pathway (responsible for the destruction of pancreatic β cells) to the anti-inflammatory T helper 2 (Th2) pathway. Thus, vitamin D is believed to be protective against the development of T1D. Four VDR gene polymorphisms (BsmI [rs1544410], FokI [rs2228570], ApaI [rs7975232] and TaqI [rs731236]) have been identified and shown to be associated with the development of T1D in different population groups. In addition, polymorphisms in vitamin D metabolising enzyme genes (CYP2R1 [rs10741657] and CYP27B1 [rs10877012]) have been associated with T1D. To our knowledge, there is no data on the association of these polymorphisms in the South African Indian and White populations. Therefore, the aim of this study was to determine whether polymorphisms in the genes regulating vitamin D function and metabolism play a role in the aetiology of T1D in the South African Indian and White populations. In addition, this study aimed to determine whether circulating vitamin D levels are associated with the development of T1D. Methods: Indian (83 T1D patients and 88 control participants) and White participants (106 T1D patients and 87 control participants) were recruited from the Gauteng and Durban regions in South Africa. All participants were genotyped by polymerase chain reaction- restriction fragment length polymorphisms (PCR-RFLP) for the VDR and vitamin D metabolising enzyme gene polymorphisms. Vitamin D levels were measured using the ClinRep kit on an high pressure liquid chromatography (HPLC) instrument. Zinc transporter 8 (ZnT8) autoantibody positivity was measured in all participants by EuroImmun enzyme linked immunosorbent assay (ELISA). Glucose concentrations were measured with the Cobas 6000 analyser. VDR mRNA expression levels were measured by quantitative real time PCR in a subset of the White population. Results: The median age at diagnosis was 13.0 years with a mean duration of 11.7 years in the Indian T1D cohort. The median age at diagnosis in the White T1D patients was 20.0 years with a mean duration of 21.8 years. ZnT8 autoantibodies were only detected in 21.3% of the Indian T1D and 23.6% of the White T1D patients. In the Indian population, the A alleles of BsmI, ApaI and CYP2R1 polymorphisms showed significantly higher frequencies in T1D patients as compared to controls (p = 0.023, p = 0.009 and p <0.001, respectively). Indian control participants had significantly fewer VDR and vitamin D metabolising enzyme gene risk alleles than T1D patients (p = 0.027 and p = 0.016, respectively). The majority of the White population (60.2%) and only 28.4% of the Indian population had sufficient levels of vitamin D. In our cohort, low levels of vitamin D were not associated with T1D. In the total study population, Indian ethnicity and CYP2R1 GG/GA genotype were observed to significantly contribute to lower vitamin D levels (p <0.001 and p = 0.026, respectively). Conclusion: VDR BsmI and ApaI polymorphisms and the CYP2R1 vitamin D metabolising enzyme gene polymorphism are associated with the development of T1D in the South African Indian population. In addition, increasing numbers of risk alleles were associated with T1D in the Indian cohort. Polymorphisms in the VDR gene may alter its structure preventing the binding of vitamin D. Alternatively, it could result in reduced transcription of the VDR. Since vitamin D exerts its immunoregulatory effects through the VDR, this lack of VDR activation may result in the upregulation of pro-inflammatory cytokines, β cell destruction and ultimately the development of T1D. Polymorphisms in the CYP2R1 gene may lead to reduced activity of the 25 hydroxylase enzyme and hence reduced production of the active vitamin D metabolite. Thus, reduced vitamin D levels will lead to T1D due to failure of the activation of the vitamin D signalling cascade.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Science in Medicine Johannesburg 2019